Role of hemostatic factors in hepatic injury and disease: animal models de‐liver. (10th May 2016) - Kopec, A. K.; Joshi, N.; Luyendyk, J. P.
Summary: Chronic liver damage is associated with unique changes in the hemostatic system. Patients with liver disease often show a precariously rebalanced hemostatic system, which is easily tipped towards bleeding or thrombotic complications by otherwise benign stimuli. In addition, some clinical studies have shown that hemostatic system components contribute to the progression of liver disease. There is a strong basic science foundation for clinical studies with this particular focus. Chronic and acute liver disease can be modeled in rodents and large animals with a variety of approaches, which span chronic exposure to toxic xenobiotics, diet‐induced obesity, and surgical intervention. These experimental approaches have now provided strong evidence that, in addition to perturbations in hemostasis caused by liver disease, elements of the hemostatic system have powerful effects on the progression of experimental liver toxicity and disease. In this review, we cover the basis of the animal models that are most often utilized to assess the impact of the hemostatic system on liver disease, and highlight the role that coagulation proteases and their targets play in experimental liver toxicity and disease, emphasizing key similarities and differences between models. The need to characterize hemostatic changes in existing animal models and to develop novel animal models recapitulating the coagulopathy of chronic liver disease is highlighted. Finally, we emphasize the continued need to translate knowledge derived from highly applicable animal models to improve our understanding of the reciprocal interaction between liver disease and the hemostatic system in patients.